2018
DOI: 10.1155/2018/3232105
|View full text |Cite
|
Sign up to set email alerts
|

Primary Carnitine Deficiency: A Rare, Reversible Metabolic Cardiomyopathy

Abstract: A 24-year-old female with a diagnosis of primary carnitine deficiency, a rare inherited metabolic disorder predominantly described in the paediatric literature that causes cardiomyopathy, presented for evaluation after three months of nonadherence with prescribed carnitine therapy. Initial echocardiography demonstrated severe left ventricular dilation (104 ml/m2) (normal < 76 ml/m2) with moderate systolic dysfunction (ejection fraction 40%) and severe right ventricular dilation with mild systolic dysfunction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 5 publications
1
17
0
Order By: Relevance
“…L-carnitine is a well-established treatment for LSM's, including primary carnitine deficiency [11]. These patients can show a rapid reversal of clinical symptoms within one month [22][23][24] and, consistent with our murine data, L-carnitine needs to be maintained to provide ongoing symptomatic relief [9,25]. While it can be challenging to extrapolate clinical timelines from animal data, the effects in our model were seen rapidly-as early as 4 weeks in the mice.…”
Section: Plos Onementioning
confidence: 99%
“…L-carnitine is a well-established treatment for LSM's, including primary carnitine deficiency [11]. These patients can show a rapid reversal of clinical symptoms within one month [22][23][24] and, consistent with our murine data, L-carnitine needs to be maintained to provide ongoing symptomatic relief [9,25]. While it can be challenging to extrapolate clinical timelines from animal data, the effects in our model were seen rapidly-as early as 4 weeks in the mice.…”
Section: Plos Onementioning
confidence: 99%
“…However, there has been a report of CD25+ pericardial mast cells producing a lifethreatening cardiac tamponade in a 59-year-old male with systemic mastocytosis for 30 years. 10 Patients with mast cell activation disorders have been reported to have left ventricular diastolic dysfunction. 10 Carnitine as a primary deficiency can be autosomal recessive, or a secondary deficiency due to kidney losses or nutritional deficiencies; it occurs through mutations in the CLC22A5 gene that result in a missing or defective OCTN2 protein.…”
Section: Discussionmentioning
confidence: 99%
“…According to the evidence from children and adults, cardiomyopathy in PCD responds well to carnitine supplementation, and is rapidly reversible under treatment [12,13]. Wang et al reported a series of six children with PCD who all presented with severe left ventricular dysfunction.…”
Section: Discussionmentioning
confidence: 99%